1976
DOI: 10.1289/ehp.761439
|View full text |Cite
|
Sign up to set email alerts
|

Potential hazards of fumigant residues.

Abstract: A spectrum of fumigants (primarily ethylene dibromide, 1,2-dibromo-3-chloropropane, ethylene oxide, symdibromotetetrachloroethane, 1,3-dichloropropene, dichlorovos, carbon tetrachloride, methyl bromide) as well as their degradation products in foodstuffs and soil have been examined mainly in regard to the potential mutagenicity of their residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Epoxides and phosphines have strong cell toxic effects: Ethylene oxide (EO) is used for sterilization of various materials (textiles, medical supplies, etc.) because of its antimicrobial, antiviral and antifungal effects [44,45]). These effects are caused by the alkylation of DNA and RNA strands of organisms by the EO, which irreversibly inhibits cellular metabolism [46].…”
Section: Discussionmentioning
confidence: 99%
“…Epoxides and phosphines have strong cell toxic effects: Ethylene oxide (EO) is used for sterilization of various materials (textiles, medical supplies, etc.) because of its antimicrobial, antiviral and antifungal effects [44,45]). These effects are caused by the alkylation of DNA and RNA strands of organisms by the EO, which irreversibly inhibits cellular metabolism [46].…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological studies have indicated the undesirable nature of residues of some parent compounds, and since less is known of the effects of alteration products or metabolites, further studies are indicated (Fishbein 1976). Recent analytical work has demonstrated that organic bromides may remain associated with the commodity for some time after fumigation.…”
Section: Analysis and Significance Of Fumigant Residuesmentioning
confidence: 99%
“…Recent analytical work has demonstrated that organic bromides may remain associated with the commodity for some time after fumigation. Toxicological studies have indicated the undesirable nature of residues of some parent compounds, and since less is known of the effects of alteration products or metabolites, further studies are indicated (Fishbein 1976).…”
Section: Analysis and Significance Of Fumigant Residuesmentioning
confidence: 99%